3D-Printed Microfluidics and Potential Biomedical Applications - Prabhakar, Priyanka; Sen, Raj Kumar; Dwivedi, Neeraj; Khan, Raju; Solanki, Pratima R.; Srivastava, Avanish Kumar; Dhand, Chetna (Frontiers in Nanotechnology, 2021)
3D printing is a smart additive manufacturing technique that allows the engineering of biomedical devices that are usually difficult to design using conventional methodologies such as machining or molding. Nowadays, 3D printed microfluidics has gained enormous attention due to their various advantages including fast production, cost-effectiveness, accurate designing of a range of products even geometrically complex devices. In this review, we focused on the recent significant findings in the field of 3D printed microfluidic devices for biomedical applications. 3D printers are used as fabrication tools for a broad variety of systems for a range of applications like diagnostic microfluidic chips to detect different analytes e.g. glucose, lactate, glutamate, etc. and the biomarkers related to different clinically relevant diseases e.g. malaria, prostate cancer, and breast cancer, etc. 3D printers can print various materials (inorganic and polymers) with varying density, strength and chemical properties that provide users with a broad variety of strategic options. In this paper, we have discussed potential 3D printing techniques for the fabrication of microfluidic devices that are suitable for biomedical applications. Emerging diagnostic technologies using 3D printing as a method for integrating living cells or biomaterials into 3D printing are also reviewed.